Inhibition of bromodomain and extra‐terminal proteins increases sensitivity to venetoclax in chronic lymphocytic leukaemia. Issue 2 (10th December 2019) - Carrà, Giovanna; Nicoli, Paolo; Lingua, Marcello Francesco; Maffeo, Beatrice; Cartellà, Antonio; Circosta, Paola; Brancaccio, Mara; Parvis, Guido; Gaidano, Valentina; Guerrasio, Angelo; Saglio, Giuseppe; Taulli, Riccardo; et al.
Abstract: The development of drugs able to target BTK, PI3k‐delta and BCL2 has dramatically improved chronic lymphocytic leukaemia (CLL) therapies. However, drug resistance to these therapies has already been reported due to non‐recurrent changes in oncogenic pathways and genes expression signatures. In this study, we investigated the cooperative role of the BCL2 inhibitor venetoclax and the BRD4 inhibitor JQ1. In particular, we found that JQ1 shows additional activity with venetoclax, in CLL cell lines and in ex vivo isolated primary CD19 + lymphocytes, arguing in favour of combination strategies. Lastly, JQ1 is also effective in venetoclax‐resistant CLL cell lines. Together, our findings indicated that the BET inhibitor JQ1 could be a promising therapy in CLL, both as first‐line therapy in combination with venetoclax and as second‐line therapy, after the emergence of venetoclax‐resistant clones.